2009
DOI: 10.1111/j.1753-4887.1987.tb06082.x
|View full text |Cite
|
Sign up to set email alerts
|

Iron in Nutrition Vii. Copper as a Supplement to Iron for Hemoglobin Building in the Rat

Abstract: Editor's Note: This paper from Professor Elvehjem's group at the University of Wisconsin was the first to demonstrate the essentiality of copper for hemopoiesis in an animal. Forty years later Professor George Graham's group at Johns Hopkins University found signs of copper deficiency in malnourished infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 0 publications
0
32
0
3
Order By: Relevance
“…Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. rat work at the University of Wisconsin (Hart et al, 1928). However, a role for Cu in explaining anemia was suggested in humans 80 years earlier (Fox, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. rat work at the University of Wisconsin (Hart et al, 1928). However, a role for Cu in explaining anemia was suggested in humans 80 years earlier (Fox, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to Fe and folic acid, lucerne leaf concentrate contains nutritionally beneficial amounts of b-carotene (54 % of RDA), vitamin E (66 % of RDA), Ca (26 % of RDA) and Cu (8 % of RDA; Table 1). Evidence for synergistic effects of these micronutrients on Fe and folic acid supplementation for the treatment of anaemia is inconsistent (15)(16)(17)(18)(19) , although it is known that Cu has a role in haematopoiesis (20) and vitamin A and b-carotene have been shown to improve Fe absorption, possibly by preventing the inhibitory effects of phytates and polyphenols (21,22) . Regardless of these possible synergies, it is indisputable that girls approaching childbearing age would benefit from the correction of other prevalent nutritional deficiencies, particularly of vitamin A (23)(24)(25)(26)(27) and Ca (28) .…”
Section: Discussionmentioning
confidence: 99%
“…Copper's essentiality was first discovered in 1928, when it was demonstrated that rats fed with copper-deficient milk diet were unable to produce sufficient red blood cells. 4 Cataract is clouding of the lens in the eye leading to a decrease in vision. It can affect one or both eyes.…”
Section: Introductionmentioning
confidence: 99%